Real and Monetary Policy Convergence: EMU Crisis to the CFA Zone - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
Purpose A major lesson of the EMU crisis is that serious disequilibria result from regional monetary arrangements not designed to be robust to a variety of shocks. The purpose of this paper is to assess these disequilibria within the CEMAC, UEMOA and CFA zones. Design/methodology/approach In the assessments, monetary policy targets inflation and financial dynamics of depth, efficiency, activity and size while real sector policy targets economic performance in terms of GDP growth. We also provide the speed of convergence and time required to achieve a 100% convergence. Findings But for financial intermediary size within the CFA zone, findings for the most part support only unconditional convergence. There is no form of convergence within the CEMAC zone. Practical implications The broad insignificance of conditional convergence results have substantial policy implications. Monetary and real policies which are often homogenous for member states are thwarted by heterogeneous structural and institutional characteristics which give rise to different levels and patterns of financial intermediary development. Therefore member states should work towards harmonizing cross-country differences in structural and institutional characteristics that hamper the effectiveness of monetary policies. Originality/value The paper provides warning signs to the CFA zone in the heat of the Euro zone crises.
Keywords: F15; F36; F42; O55; P52; 330; CFA Zone; Currency Area; Convergence; Policy Coordination